Developing digital teaching module with problem-based learning integrated to virtual lab on electricity - Amelia, Rizki (Jurnal Ilmiah Pendidikan Dasar, 2024)
Science learning is empirical learning that involves the process of investigation. However, limited facilities and infrastructure, and the unavailability of laboratories are obstacles in the process of investigating science learning. Traditional laboratories require much time, cost and performance, so using virtual laboratories can be an alternative in science learning. The problem-based learning model can guide the use of virtual laboratories in science learning. Thus, this study aims to develop and test the feasibility of digital teaching material products based on problem-based learning integrated with virtual laboratories on electricity material for PGMI students. The product development process refers to the Lee & Owens development model, which consists of analysis, design, development, implementation and evaluation. The data collection instrument consists of a media validation test instrument, material validation test and readability test in the form of a questionnaire with a Likert scale. The results of the media validation test showed a percentage score of 92.33% with very valid criteria. In comparison, the readability test generated a score of 83.25 with very valid criteria. Thus, digital teaching materials based on problem-based learning integrated with virtual labs on electricity material are proven to be valid and feasible for use in science learning for PGMI students